Automated Sequential Pushing of Micro Objects By Using Adaptive Controller - Mohsen Shahini; William W. Melek; John T.W. Yeow (Institute of Advanced Engineering and Science, 2013)
This paper focuses on precision automated pushing of multiple micro objects. An adaptive control system is proposed to accurately push and position the micro objects on a substrate. Each micro object exhibits different characteristics in terms of the surface micro forces governing the manipulation process. The controller is designed to compensate for the effect of the micro forces whose aggregated magnitude varies during the process. An experimental setup is designed to validate the performance of the proposed controller. The results of the experiments confirm that the proposed adaptive controller is capable of learning to adjust its parameters effectively, when the surface micro forces change under varying surface and ambient conditions.